2014
DOI: 10.1155/2014/431858
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Preclinical Pharmacology of theγ-Secretase Modulator BMS-869780

Abstract: Alzheimer's disease is the most prevalent cause of dementia and is associated with accumulation of amyloid-β peptide (Aβ), particularly the 42-amino acid Aβ1-42, in the brain. Aβ1-42 levels can be decreased by γ-secretase modulators (GSM), which are small molecules that modulate γ-secretase, an enzyme essential for Aβ production. BMS-869780 is a potent GSM that decreased Aβ1-42 and Aβ1-40 and increased Aβ1-37 and Aβ1-38, without inhibiting overall levels of Aβ peptides or other APP processing intermediates. BM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 77 publications
0
18
0
Order By: Relevance
“…One of their lead compounds, 31 (BMS-869780),105 has been described as their first optimized candidate. This GSM replaces the typical methyl imidazole with a chloroimidazole.…”
mentioning
confidence: 99%
“…One of their lead compounds, 31 (BMS-869780),105 has been described as their first optimized candidate. This GSM replaces the typical methyl imidazole with a chloroimidazole.…”
mentioning
confidence: 99%
“…The novel GSMs BMS-932481 and BMS-986133 were prepared at Bristol-Myers Squibb, Wallingford, CT, using methods reported in Bristol-Myers Squibb patents ( Boy et al 2014a , b ). The γ -secretase inhibitors (GSIs) used for comparisons in some experiments, (R)-4-(2-(1-((4-chloro-N-(2,5-difluorophenyl)phenyl)sulfonamido)ethyl)-5-fluorophenyl)butanoic acid (BMS-299897; Barten et al, 2005 ) and (R)-2-((4-chloro-N-(2-fluoro-4-(1,2,4-oxadiazol-3-yl)benzyl)phenyl)sulfonamido)-3-cyclopropylpropanamide (BMS-698861; Toyn et al, 2014 ), have been described previously.…”
Section: Methodsmentioning
confidence: 99%
“…In overview, A β peptides were quantified using a range of different immunoassays, using antibodies that are specific for the free C-terminal amino acids of A β 1-42, A β 1-40, A β 1-38, or A β 1-37 ( Toyn et al, 2014 ). Immunoassays for A β 1-x used antibodies that are not selective for the free C-terminal amino acid, and therefore measured the sum of the A β peptides including A β 1-42, A β 1-40, A β 1-38, and A β 1-37.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…AstraZeneca has published structurally related GSMs including AZ4800, which has an Ab42 IC 50 of 26 nM and lowered brain Ab42 by 46% when dosed orally at 130 mg/kg (Borgegard et al 2012). BMS incorporated an aminotriazole core and a chloroimidazole A-ring in place of the commonly used 4-methylimidazole to afford potent GSMs such as BMS-869780 (Ab42 IC 50 ¼ 5.6 nM) (Toyn et al 2014). PK/PD modeling indicated that a dose of 700 mg would be required to achieve a 25% reduction of Ab42 in the human brain.…”
Section: Non-nsaid Heterocyclic Gsmsmentioning
confidence: 99%